Dialectics of Job Stress and Organizational Peace. A critical study on the Management of Personnel Motivation in Enterprise Marketing in the Face of the Ukrainian War Experience - Tetiana Kornieieva; Oksana Syniuk; Nataliia Shevchenko; Nadiia Marushko (Clío)
In philosophical terms, the dialectic between work stress and organizational peace focuses on how the war in Ukraine affects the management of personal motivation in corporate marketing. Accordingly, the overall objective of this study is to analyze how job stress affects employee motivation and, in turn, conditions organizational effectiveness in crisis situations, resulting from the war. The methods used included a mixture of qualitative approaches, a reading of the texts and contexts that account for this complex reality, together with open interviews with two experts on the subject. The contribution of this research is to provide recommendations to improve stress management and create a work environment that promotes organizational peace and personal motivation, despite the war, thus facilitating effective recovery during a prolonged crisis. In conclusion, this critical analysis shows that stress at work not only has an impact on the mental health of workers, but also directly affects productivity and the organizational environment, with political and economic consequences for society.